(untitled) (Innovaciones Educativas, 2021)
Mathematics Education, as a scientific field, analyzes and improves this discipline’s teaching and learning, tackling a variety of issues, problems, and obstacles concerning teaching and learning, teachers and learners, as well as its socio-cultural, political, and economical contexts, among many others. In their quest for solutions and answers, teachers and researchers face different challenges to implement research and innovation actions that will improve Math learning in students. In this article, we briefly reflect on three of the current challenges, related to the use of technology, attention to mathematically gifted students, and teacher training. We discuss some aspects of each challenge, and we also provide references for further reflection on the topic.